Synthesis, characterisation and biological activities of Ru(III), Mo(V), Cd(II), Zn(II) and Cu(II) complexes containing a novel nitrogen-sulphur macrocyclic Schiff base derived from glyoxal - Chah, Chee Keong; Ravoof, Thahira B. S. A.; Veerakumarasivam, Abhimanyu (Universiti Putra Malaysia Press, 2018)
A novel nitrogen-sulphur macrocyclic Schiff base, 4,11,20,27-tetrathioxo-3,12,19,28-tetrathia-5,6,9,10,21,22,25,26-octaazatricyclo[28.2.2.214,17]hexatriaconta 1(33),6,8,14(36),15,17(35),22,24,30(34),31-decaene-2,13,18,29-tetraone (TGSB) derived from terephthaloyl-bis-dithiocarbazate (TDTC) and glyoxal (ethane-1,2-dione) is synthesised via condensation. Metal complexes are formed by reacting the Schiff base with various metal salts such as Ru(III), Mo(V), Cd(II), Zn(II) and Cu(II). The complexes are expected to have a general formula of M2L or M3L with a square planar or square pyramidal geometry. These compounds were characterised by various physico-chemical and spectroscopic techniques. From the data, it is concluded that the azomethine nitrogen atom and the thiolate sulphur atom from the ligand are bonded to the metal ion. In the IR spectra of the complexes, the presence of the C=N band in the region of 1600 cm-1 indicates the successful formation of the Schiff base. The structures of the Schiff base and metal complexes are confirmed via FT-IR, GC-MS and NMR spectroscopic analysis. The magnetic susceptibility measurements, electronic spectral data and molar conductivity analysis support the desired geometry of the complexes. The Schiff base and its metal complexes are evaluated for their biological activities against the invasive human bladder carcinoma cell line (EJ-28) and the minimum-invasive human bladder carcinoma cell line (RT-112). The RuTGSB and CdTGSB complexes showed selective activity against RT-112.